2010
DOI: 10.1159/000314787
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues in Health and Education in Asia-Pacific: A Focus on Speech-Language Pathology

Abstract: The purpose of this paper is to present some emerging issues in health and education in the Asia-Pacific region. Special attention will be given to the education of speech-language pathologists (SLP) and to service provision for the people with communicative disorders whenever possible. Information on the education of SLP in Asia-Pacific is not easy to gather because of the geographical distances between areas, language differences in the data compiled and the lack of consistent collaboration and information e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…2017, Wylie et al . 2012) and similar limitations can be found in Asia and other parts of Africa (Cheng 2010, Chu et al . 2019, Haas 2015, Pillay et al .…”
Section: Social Inequalities In the Receipt Of Health And Social Caresupporting
confidence: 58%
“…2017, Wylie et al . 2012) and similar limitations can be found in Asia and other parts of Africa (Cheng 2010, Chu et al . 2019, Haas 2015, Pillay et al .…”
Section: Social Inequalities In the Receipt Of Health And Social Caresupporting
confidence: 58%
“…In several countries in South America, and in some areas of India, audiology, and speech and language therapists are one profession, with a subspecialization. 42,43 In some instances speech and language therapists have trained abroad. For example, therapists in Paraguay have trained in Brazil, therapists in Bolivia and Venezuela in the United States, 42 and therapists in the Philippines and Singapore in Australia, the United Kingdom and the United States.…”
Section: Deaf Servicesmentioning
confidence: 99%
“…For example, therapists in Paraguay have trained in Brazil, therapists in Bolivia and Venezuela in the United States, 42 and therapists in the Philippines and Singapore in Australia, the United Kingdom and the United States. 43 Other examples document programmes in speech and language therapy that have been established with foreign assistance: for example in Sri Lanka and Uganda with volunteers from the United Kingdom, 44,45 in Togo with volunteers from France, 46 and in Viet Nam with volunteers from Australia. 47 The institutions in Togo and Uganda have subsequently become regional centres in Africa, training speech and language therapists specialists in Benin, Gabon and Mali, 46 and in Rwanda and the United Republic of Tanzania, respectively.…”
Section: Deaf Servicesmentioning
confidence: 99%
“…It has been reported that there are almost as many Fijian-born doctors working in Australia and New Zealand as there are in Fiji (Negin, 2008). Cheng (2010) presents an initiative for building a locally trained rehabilitation workforce; a collaborative model with a US mainland university and the University of Guam to deliver a Master's level speech pathology course in Guam. This prevents the need for further training abroad, leading to the observation that if rehabilitation personnel are trained locally they may be more likely to remain in their own countries.…”
Section: Available and Culturally Relevant Workforcementioning
confidence: 99%